2021
DOI: 10.1007/s12671-021-01663-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness-Based Stress Reduction on Health and Social Care Education: a Cohort-Controlled Study

Abstract: Objectives Mindfulness practice has been recommended as part of health and social care education and training because of its potential benefits in fostering clinical skills and attitudes, increasing self-care, and reducing the effect of stress in education and occupation. The objectives of this study were to evaluate the effects of a mindfulness-based stress reduction (MBSR) program on stress, physical distress, job burnout, work engagement, and empathy for health and social care education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…In fact, nurses and social workers showed significantly higher total scores than clinical psychologists, and there were significant differences in subscale scores among professionals. Results and reviews conducted to date have suggested that the scale was a useful measure and predictor of stress [41]. Specifically, in this study, the PSS was administered to professionals in the educational setting; indeed, it was found that there are contexts such as education, service, and helping professions in which the immateriality of the work product can upset the individual.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, nurses and social workers showed significantly higher total scores than clinical psychologists, and there were significant differences in subscale scores among professionals. Results and reviews conducted to date have suggested that the scale was a useful measure and predictor of stress [41]. Specifically, in this study, the PSS was administered to professionals in the educational setting; indeed, it was found that there are contexts such as education, service, and helping professions in which the immateriality of the work product can upset the individual.…”
Section: Discussionmentioning
confidence: 86%
“…Mindfulness relates to the ability to stay attuned to the present, rather than ruminating about the past or worrying about the future. A total of six interventions adopted this approach (two randomized controlled trials, four quasiexperimental studies; Clarkson et al, 2019;de Vibe et al, 2013;Lo et al 2021;Modrego-Alarcon et al, 2021;O'Driscoll et al, 2019a;O'Driscoll et al, 2019b). The majority were delivered in person (5/6) and ranged from 4 to 8 weeks in length.…”
Section: Mindfulness-based Stress Reductionmentioning
confidence: 99%
“…Work engagement is an important indicator of employee wellbeing and organizational performance (Seppälä et al, 2009;Xanthopoulou et al, 2009) but this construct has been infrequently studied in mindfulness intervention research (Malinowski and Lim, 2015;Bartlett et al, 2019). Recent evidence on the face-to-face delivery of MBIs such as MBSR indicate that it can be effective in increasing resilience (Klatt et al, 2021) and work engagement at the same time as reducing burnout (Lo et al, 2021) but it is currently unclear whether similar benefits can be derived from scalable and affordable brief online MBIs. Our findings that mindfulness training is clearly associated with higher engagement-and in particular, patterns of adaptive engagement-thus offer an additional contribution to the literature but further research and different methodology are required to establish whether this relationship is causal.…”
Section: Post-intervention Changes In Mindfulness Stress and Engagementmentioning
confidence: 99%